Legal Uncertainty Due to Differences in Children's Age Limits in Legislation and Harmonization Efforts to Prevent Child Discrimination - Gultom Rosmaida Feriana; Evita Isretno Israhadi2 (Majelis: Jurnal Hukum Indonesia, 2025)
The differences in the age limits of children as stipulated in several Indonesian laws and regulations—such as the Juvenile Criminal Justice System Law (UU Sistem Peradilan Pidana Anak/SPPA), the Child Protection Law (UU Perlindungan Anak), and the Human Rights Law (UU HAM)—have created significant legal uncertainty. These inconsistencies pose serious implications for the protection of children's rights, particularly for those who are entangled in legal conflicts. One of the most critical impacts is the potential for injustice in the application of restorative justice and diversion programs, which should be guided by the principle of the best interests of the child. Discrepancies in age definitions may also result in unequal treatment in legal proceedings and hinder access to appropriate legal remedies and rehabilitation services. For instance, a child considered underage by one law may be treated as an adult under another, leading to inconsistent judicial decisions, discrimination, and psychological harm. Furthermore, this lack of regulatory harmony undermines the credibility and consistency of the justice system in handling cases involving children. The principle of legal certainty, which is fundamental in any just legal system, cannot be upheld if such foundational definitions remain fragmented. Therefore, there is an urgent need for harmonization and alignment of all regulations related to the legal age definition of a child within the Indonesian national legal framework. Establishing a uniform age standard is essential to ensure fair treatment, protect children's rights comprehensively, prevent discriminatory practices, and improve the effectiveness of restorative justice, rehabilitation, and child protection mechanisms in Indonesia.